Cytomegalovirus: A possible cause of Persistent Refractory Immune Thrombocytopenic Purpura - Shrestha, Raksha; Rondelli, Damiano; Sherpa, Mingma Thsering (Journal of Advances in Internal Medicine, 2014)
We present a case of a healthy 22 years old who presented with bruising and hematoma following a minor trauma. Investigations showed severe thrombocytopenia but complete hematological investigations did not reveal a cause. An aggressive treatment with steroids, IVIG, anti-D, splenectomy and immunosuppressant proved to be refractory. A subclinical transaminitis prompted an infectious workup which revealed Cytomegalovirus infection. Platelet count improved and remained stable after eradication of Cytomegalovirus. We conclude that infection with CMV should be ruled out in cases of severe refractory immune thrombocytopenic purpura. DOI: http://dx.doi.org/10.3126/jaim.v3i1.10704 Journal of Advances in Internal Medicine 2014;03(01):42-45